Elicitation of trustworthiness requirements for highly dexterous teleoperation systems with signal latency - Louca, Joe; Vrublevskis, John; Eder, Kerstin; Tzemanaki, Antonia (Frontiers in Neurorobotics, 2023)
ABSTRACT Teleoperated robotic manipulators allow us to bring human dexterity and cognition to hard-to- reach places on Earth and in space. In long-distance teleoperation, however, the limits of the speed of light results in an unavoidable and perceivable signal delay. The resultant disconnect between command, action, and feedback means that systems often behave unexpectedly, reducing operators’ trust in their systems. If we are to widely adopt telemanipulation technology in high-latency applications, we must identify and specify what would make these systems trustworthy. In this requirements elicitation study, we present the results of thirteen interviews with expert operators of remote machinery from four different application areas – nuclear reactor maintenance, robot-assisted surgery, underwater exploration, and ordnance disposal – exploring which features, techniques or experiences lead them to trust their systems. We found that across all applications, except for surgery, the top-priority requirement for developing trust is that operators must have a comprehensive engineering understanding of the systems’ capabilities and limitations. The remaining requirements can be summarised into three areas: improving situational awareness, facilitating operator training and familiarity, and easing the operator’s cognitive load. While the inclusion of technical features to assist the operators was welcomed, these were given lower priority than non-technical, user-centric approaches. The signal delays in the participants’ systems ranged from none perceived to 1 minute, and included examples of successful dexterous telemanipulation for maintenance tasks with a 2- second delay. As this is comparable to Earth-to-orbit and Earth-to-Moon delays, the requirements discussed could be transferable to telemanipulation tasks in space.